Factors Influencing the Results of an Unqualified Opinion (WTP) on the Financial Reports of District/City Governments in South Sumatra Province - Hasanah, Siti Lailatull; Dwitayanti, Yevi; Choiruddin, C. (Manunggal Halim Jaya, 2026)
This study aims to determine the effect of weaknesses in the internal control system (ISC), non-compliance with laws and regulations, and the age of the local government on the WTP opinion on the financial statements of district/city governments in South Sumatra province. The population in this study was all district/city governments in South Sumatra. The sampling technique used in this study was the saturated sampling method, meaning that all members of the population were sampled, and sample data were obtained from as many as 68 Financial Statements of District/City Governments in South Sumatra. This hypothesis testing used Logistic Regression with the help of SPSS 26 software. The results of this study indicate that, to some extent, the variables of ISC weaknesses and non-compliance with laws and regulations affect the WTP opinion on the financial statements of local governments. The variable of age of the local government does not affect the WTP opinion on the financial statements of local governments. Simultaneously, weaknesses in ISC, non-compliance with laws and regulations, and the age of the local government together affect the WTP's opinion on the financial statements of local governments.